Saving the Euro at the Cost of Democracy?1. (24th April 2013) - Crum, Ben
Abstract This article explores the implications of the financial crisis for the relationship between monetary integration and democratic government in the European Union (EU). As the crisis has exposed the original balance that economic and monetary union (EMU) sought to maintain between monetary integration and policy diversity to be unsustainable, the eurozone is put before the choice of one of three governance models: executive federalism, democratic federalization or EMU dissolution. Notably, these three governance models perfectly illustrate Dani Rodrik's 'trilemma of the world economy', which maintains that of the three goods – economic (and monetary) integration, the nation‐state and democratic politics – one will always have to give. In light of this, the article concludes that the present course towards executive federalism can be justified for preventing euro dissolution and recognizing the value of national self‐government. Nevertheless, it threatens to come at a democratic price. Hence, it is imperative to consider possible flanking measures that can mitigate this effect.